Functional effects of dopamine transporter gene genotypes on in vivo dopamine transporter functioning: a meta-analysis - Faraone, S V; Spencer, T J; Madras, B K; Zhang-James, Y; Biederman, J (Molecular psychiatry, 2014)
Much psychiatric genetic research has focused on a 40-base pair variable number of tandem repeats (VNTR) polymorphism located in the 3′-untranslated region (3′UTR) of the dopamine active transporter (DAT) gene ( SLC6A3 ). This variant produces two common alleles with 9- and 10-repeats (9R and 10R). Studies associating this variant with in vivo DAT activity in humans have had mixed results. We searched for studies using positron emission tomography (PET) or single-photon emission computed tomography (SPECT) to evaluate this association. Random effects meta-analyses assessed the association of the 3′UTR variant with DAT activity. We also evaluated heterogeneity among studies and evidence for publication bias. We found twelve studies comprising 511 subjects, 125 from PET studies and 386 from SPECT studies. The PET studies provided highly significant evidence that the 9R allele was associated with increased DAT activity in human adults. The SPECT studies were highly heterogeneous. As a group, they suggested no association between the 3′UTR polymorphism and DAT activity. When the analysis was limited to the most commonly used ligand, [123I]β-CIT, stratification by affection status dramatically reduced heterogeneity and revealed a significant association of the 9R allele with increased DAT activity for healthy subjects. In humans, the 9R allele of the 3′UTR polymorphism of SLC6A3 regulates dopamine activity in the striatal brain regions independent of the presence of neuropsychiatric illness. Differences in study methodology account for the heterogeneous results across individual studies.